Granger causality analysis on PLUS highway traffic network - Mohd Asrah, Norhaidah; Djauhari, Maman Abdurachman; Khamis, Azme; Mohd Salleh, Rohayu; Muhammad Fitri Avtar, Sya Sya Syahira (Science Publishing Corporation, 2018)
PLUS Malaysia Berhad (PMB) is the largest toll expressway operator in Malaysia and South East Asia. Based on this reputation, PLUS handled thousands of vehicles every day. It covers the in-coming and out-coming traffic burdens from the northern areas to the southern areas. In order to manage these traffic burdens, toll plazas are located along this highway. Previous studies revealed that some of these toll plazas are important in managing the traffic burdens. This study analyze the importance of Skudai (SKD) toll plaza in Johor from 2009 until 2013. The causal relationship between SKD toll plaza with other toll plazas in Johor is studied to determine if there is any potential correlation or relationship of SKD with other toll plazas by using the Granger causality analysis. The findings show that there is a bidirectional Granger causality between SKD and Tangkak (TGK) as well as Machap (MAC) toll plazas. Meanwhile, there is only a unidirectional Granger causality between SKD and Yong Peng Utara (YPU) and Yong Peng Selatan (YPS) toll plazas. These results benefit the PLUS highway management to identify which potential toll plazas that can increase the traffic burden out from SKD toll plaza.